The Effect of Digital Administration Training on the Work Speed of Elementary School Teachers: An Experimental Study in Kerinci Regency - Erianto Eka Putra; Ismira Ismira; Hafiz Hidayat (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Digital transformation in educational administration has intensified demands on teachers to perform administrative tasks more efficiently, yet empirical evidence on the effectiveness of structured digital administration training remains limited in the elementary school context. This study aims to analyze the effect of digital administration training on the work speed and digital skill proficiency of elementary school teachers at SD Negeri institutions in Kayu Aro Sub-district, Kerinci Regency. A quantitative explanatory research design was employed with a sample of 72 teachers selected through total sampling. Data were collected using a validated pre- and post-training performance assessment instrument—the Composite Efficiency Index (CEI)—and a 30-item structured questionnaire, and analyzed using paired-samples t-tests and simple and multiple linear regression. The findings reveal that mean CEI scores increased significantly from 54.3 to 76.8 — representing a 41.4% improvement over baseline — with a large effect size (Cohen's d = 1.69). Digital administration training significantly predicted post-training work speed (β = 0.624, p < 0.001, R² = 0.389) and digital skill proficiency (β = 0.581, p < 0.001). The combined regression model explained 51.3% of the variance in post-training work speed (F = 45.62, p < 0.001). These results affirm that structured, contextually aligned digital training is an effective instrument for improving teachers' administrative performance.